Interview with Minister Abdur Razzak (60) on the Mujib Bahini of the Bangladesh Liberation War of 1971. Interviewed by Shahriar Kabir in Dhaka, 09/09/2000 - Kabir, Shahriar.
Interview with Minister Abdur Razzak (60) on the Mujib Bahini of the Bangladesh Liberation War of 1971. Interviewed by Shahriar Kabir in Dhaka, 09/09/2000.